Hibecovirus (genus Betacoronavirus) infection linked to gut microbial dysbiosis in bats - Melville, Dominik W; Meyer, Magdalena; Risely, Alice; Wilhelm, Kerstin; Baldwin, Heather J; Badu, Ebenezer K; Nkrumah, Evans Ewald; Oppong, Samuel Kingsley; Schwensow, Nina; Tschapka, Marco; Vallo, Peter; Corman, Victor M; et al. (ISME communications, 2025)
Little is known about how zoonotic virus infections manifest in wildlife reservoirs. However, a common health consequence of enteric virus infections is gastrointestinal diseases following a shift in gut microbial composition. The sub-Saharan hipposiderid bat complex has recently emerged to host at least three coronaviruses (CoVs), with Hipposideros caffer D appearing particularly susceptible to Hibecovirus CoV-2B infection. In this study, we complement body condition and infection status data with information about the gut microbial community to understand the health impact of CoV infections in a wild bat population. Of the three CoVs, only infections with the distantly SARS-related Hibecovirus CoV-2B were associated with lower body condition and altered the gut microbial diversity and composition. The gut microbial community of infected bats became progressively less diverse and more dissimilar with infection intensity, arguing for dysbiosis as per the Anna Karenina principle. Putatively beneficial bacteria, such as Alistipes and Christensenella, decreased with infection intensity, while potentially pathogenic bacteria, namely Mycoplasma and Staphylococcus, increased. Infections with enterically replicating viruses may therefore cause changes in body condition and gut dysbiosis with potential negative health consequences even in virus reservoirs. We argue that high-resolution data on multiple health markers, ideally including microbiome information, will provide a more nuanced picture of bat disease ecology.
Keywords: Anna Karenina principle; coronavirus; microbiome; Ghana; Chiroptera